An evaluation of seed zone delineation using phenotypic and population genomic data on black alder Alnus glutinosa. Issue 5 (21st July 2014) - De Kort, Hanne; Mergeay, Joachim; Vander Mijnsbrugge, Kristine; Decocq, Guillaume; Maccherini, Simona; Kehlet Bruun, Hans Henrik; Honnay, Olivier; Vandepitte, Katrien; Bugmann, Harald
Summary Delineation of seed zones or provenance regions to preserve local adaptation is a common practice in forestry and restoration, as locally adapted plants generally possess relatively high levels of productivity and resistance. Provenance trials typically quantify the degree of phenotypic divergence among individuals and populations raised under common conditions, which is time‐consuming and potentially confounded by phenotypic plasticity and maternal effects. Here, we put forward population genomics, the screening of individual genomes for the genetic signature of adaptation, as a fast and reliable strategy to evaluate seed zone delineation. To illustrate the value of this approach, we quantified the degree of genomic adaptation within and among Belgian black alder Alnus glutinosa provenances and compared results with traditional provenance trials. Distant European reference regions were included to validate the approaches, as larger environmental differences at a European scale are expected to result in larger adaptive responses. Local provenances did not perform better than foreign provenances at the scale of Belgian seed zones, in contrast to the comparisons with the distant European regions. A significant site effect indicated that plastic responses rather than local adaptation explain phenotypic differences among seed zones. The common garden revealed little evidence for adaptation for all measured traits, both among seed zones and among distant regions. The number and strength of genetic outliers was not significantly larger among Belgian seed zones than within these seed zones, but was significantly larger between Belgian seed zones and the distant European reference regions. Synthesis and applications. The lack of adaptive divergence among Belgian seed zones supports an expansion of current provenance regions into larger seed zones. The results also show that population genomics can be an accurate and time‐efficient resource to assist decisions on seed sourcing. This highlights the importance of raising awareness of the potential benefits of this novel approach among policy makers, foresters and restoration practitioners.